Zupani of Usore, Soli and Treboticha - Smiljanić, Aranđel (Historical Thought, 2025)
This paper presents data concerning the title of zupan and its holders from the lands of Usora and Soli, as well as from the parish of Trebotich, given that during a certain period of the 14th century they constituted a distinct administrative unit within the Bosnian state. The central part of the paper contains a description of the activities of six zupans from this region (Budos, Poruchen Pribislavich, Juraj Tihchinovich, Ivahn Pribilovich, Novak Ivahnich, and Dragich Poznanovich), who are recorded as witnesses in the charters of Bosnian rulers from the 1220s to the 1370s. In doing so, the author pays special attention to their title, the time and place of their appearance in the charters.